The National Science Olympiad and Its Impact on Improving the Quality of Education - Pattipeilohy, Poltjes; Akyuwen, Frandy; Cindy, Agustin Hanivia; Pattiasina, Johan (LP. Ma'arif Janggan Magetan, 2024)
This study aims to clearly describe the implementation of the National Science Olympiad organized by the Faculty of Mathematics and Natural Sciences, Pattimura University Ambon and its impact on improving the quality of education. The focus of the research is the process of organizing the national science olympiad, and its impact on improving the quality of education. This study uses qualitative research. The data collection methods are observation, interviews, and documentation. The results of the study show that the National Science Olympiad involves elementary, junior high, high school, and vocational school students throughout Maluku with a total of 3,323 participants. The region, which is dubbed as a sea-based archipelago province, is not a barrier for students to compete to be the best. As a result, when students excel in a competition, the quality of education will be better. The supporting factors for the implementation of the National Science Olympiad are internal and external factors. Internal factors come from within students, while external factors come from the school environment and family environment. The inhibiting factors are the cost and location of the competition. Some of the implications of this research: Education Policy Design; Curriculum development; Teacher Training and Development; Increasing Student Participation; and Extracurricular Program Development. Research at the National Science Olympiad has made significant contributions to the following aspects: Development of Academic Knowledge; Improvement of Educational Practices; Support for Policy Makers; Motivation for students; and Strengthening Research Networks.